2018
DOI: 10.1103/physrevfluids.3.074301
|View full text |Cite
|
Sign up to set email alerts
|

Rheological response of nonspherical granular flows down an incline

Abstract: We present an extensive numerical and experimental study, investigating a threedimensional (3D) granular flow of elongated particles down an inclined plane. Similarly to sheared systems, the average particle orientation is found to enclose a small angle with the flow direction. In the bulk, this behavior is independent of the shear rate. At the surface, however, the particles move in more dilute conditions, and the average orientation strongly depends on the shear rate. A systematic numerical study varying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 62 publications
3
30
0
Order By: Relevance
“…It would be important to test the limitations of this approach when different conditions are used such as twodimensional silos; silos, orifices, and particles with different shapes; hoppers; bumpy walls; use of an overweight; and use of soft and/or deformable grains. In particular, recent simulations with spherocylinders [26] have shown that μ(I ) depends on aspect ratio, which should have an impact on the flow rate. Also interesting is the potential application to suspensions and submerged grains passing through constrictions since there are recent developments that indicate that the μ(I ) rheology is suitable to describe the flow in these systems [27,28] silo discharges using overweights have shown nonconstant flow rates during discharge [6,29].…”
Section: Discussionmentioning
confidence: 99%
“…It would be important to test the limitations of this approach when different conditions are used such as twodimensional silos; silos, orifices, and particles with different shapes; hoppers; bumpy walls; use of an overweight; and use of soft and/or deformable grains. In particular, recent simulations with spherocylinders [26] have shown that μ(I ) depends on aspect ratio, which should have an impact on the flow rate. Also interesting is the potential application to suspensions and submerged grains passing through constrictions since there are recent developments that indicate that the μ(I ) rheology is suitable to describe the flow in these systems [27,28] silo discharges using overweights have shown nonconstant flow rates during discharge [6,29].…”
Section: Discussionmentioning
confidence: 99%
“…While in volcanology the Inertial number is not (generally) used to scale experiments, it is an essential parameter to ensure scaling of the mean particle rearrangement timescale over the flow deformation timescale and it was shown to control granular flow rheology (Andreotti et al, 2013;Forterre & Pouliquen, 2008). While traditionally the inertial number is only used to describe spherical particles, recent studies suggest that it is valid also for nonspherical particles (Hidalgo et al, 2018;Nagy et al, 2017). Here, we assume 10.1029/2018JB016874 Journal of Geophysical Research: Solid Earth that the inertial number can be used to describe unsteady concentrated volcanic mixtures, since the inertial number was successfully used in dam-break simulations to describe the transient granular rheology (Martin et al, 2017).…”
Section: Bidisperse Distributions and Implications For The Modeling Omentioning
confidence: 99%
“…It should be noted that when α is taken to be a constant, then (2.6) becomes rate independent. Similar to Hidalgo et al (2018), we consider the flow of cylindrical glass rods of diameter d = 1.9 mm and length l = 3.5 d down an incline. The height of the steady state flow is set large enough compared to the size of grains, i.e.…”
Section: Flow Down An Inclinementioning
confidence: 99%
“…The orientation and velocity fields of hopper flows were measured in Guillard, Marks & Einav (2017) using advanced X-ray radiography techniques. A steady-state flow of non-spherical grains down an incline was studied in Hidalgo et al (2018) both experimentally and using DEM. This is a much simpler flow that is inhomogeneous and, as such, provides important observation that can enhance our understanding of more complex flows.…”
Section: Introductionmentioning
confidence: 99%